Clinicoetiological profile, immediate outcome and short-term follow-up of term babies with hyperbilirubinemia - C., Sonika; D., Manoj; G. R., Basanth Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal jaundice is a common cause of admission of newborns. Since bilirubin is potentially toxic to the central nervous system, early detection and appropriate management is of paramount importance. We therefore undertook this study with an objective to assess the causes, clinical correlation, immediate outcome and short term follow up for hearing and neurodevelopmental assessment in term babies with jaundice admitted in our NICU. Methods: This study was done in NICU in Bapuji Child Health Institute and Research center attached to JJMMC, Davangere. This study included 100 term infants admitted for jaundice during November 2013 to May 2015 and 6 months follow up of these infants for hearing and neurodevelopmental outcome was done. A proforma was used to collect relevant information. Results: Physiological jaundice (50%) and Blood group incompatibility (36%) were the most common causes of hyperbilirubinemia in the study. During a short term follow up i.e. 6 months, majority (97%) of the jaundiced infants had normal hearing and neurodevelopmental outcome except for 3 infants who had sensorineural hearing loss and BIND. In severe group the percentage of abnormal BERA and unfavourable neurological outcome was more when compared to moderate group, which was statistically significant. All the 3 infants who had abnormal BERA had developmental delay. Conclusions: Neonatal jaundice is a common cause of admission of newborns. Physiological jaundice was the commonest cause of neonatal hyperbilirubinaemia followed by blood group incompatability. Majority of the infants had normal BERA and normal neurodevelopmental outcome on short term follow up. A close association was found between BERA and neurodevelopmental outcome in the study. BERA is an useful neurophysiological tool for monitoring neurological complications, however it is not a useful tool to predict final neurological outcome